Serum Type 2 Cytokine Levels Are Elevated in a Chronic Pulmonary Aspergillosis Subgroup with High Serum Total Immunoglobulin E Level - Shizuka Watanabe; Junko Suzuki; Maho Suzukawa; Taku Nishimura; Masato Watanabe; Yu Enomoto; Keita Takeda; Kei Kusaka; Masahiro Kawashima; Yoshiteru Morio; Atsuhisa Tamura; Hideaki Nagai; et al. (Journal of Fungi)
A subgroup of patients with chronic pulmonary aspergillosis (CPA) exhibits elevated serum total immunoglobulin E (IgE) levels, similar to allergic bronchopulmonary aspergillosis; however, the underlying mechanisms remain unclear. This study aimed to clarify the underlying pathophysiology of the CPA subgroup with high serum total IgE levels. In this study, we prospectively collected CPA cases treated at our hospital between January and July 2022 and measured serum cytokine levels along with clinical data. We compared 34 healthy controls (HCs) and 51 patients with CPA and found significantly elevated levels of inflammatory cytokines and tissue repair and destruction-related cytokines in CPA. Among the 51 patients with CPA, 10 had total IgE levels of >500 IU/mL, whereas the remaining 41 did not. The IgE-high group exhibited significantly increased eosinophil counts and elevated levels of type 2 cytokines and pro-inflammatory cytokines. Based on these findings, patients with CPA exhibited an enhanced inflammatory response in terms of cytokines compared with HCs. In particular, the CPA subgroup with high total IgE levels may have an underlying enhancement of type 2 inflammation. Our study provides insights into the potential novel pathomechanisms of CPA and may contribute to the development of new treatment strategies.